A high uniformity optical fiber image invertor and preparation method thereof
By preparing a high-uniform optical fiber inverter, the matching drawing technology of high-refractive core material glass and low-refractive leather material glass is solved, and the high-definition imaging effect is achieved.
Patent Information
- Application Number
- CN202211102584.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-09
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-09-09
AI Technical Summary
The contrast and clarity of existing fiber optic image transmission components are insufficient, resulting in low-light night vision devices being low in imaging quality and cannot meet the application needs of high-definition.
A high uniform fiber inverter is used to prepare an optical fiber inverter. By matching a core glass rod with a high refractive index and a leather glass tube with a low refractive index, the monofilament and light absorption wire are drawn, and the optical fiber board with excellent optical performance is formed through hot melt compression molding and torsion molding.
The contrast and clarity of the optical fiber image transmission element are improved, and the imaging effect with high definition is achieved, and the high resolution and excellent fixed pattern noise performance are achieved.
Smart Images

Figure CN115469395B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of manufacturing optical fiber image transmission elements, and in particular to a high-uniformity optical fiber image inverter and a preparation method thereof. Background Art
[0002] As we all know, low-light-level night vision technology plays a very important role in soldiers' observation and combat at night. Low-light-level night vision devices, which are widely used in the field of night vision, have the ability to observe and aim at low-light conditions at night. They have the characteristics of high resolution and good stereoscopic vision. They are the main equipment for soldiers' night combat and can ensure that soldiers can complete the tasks of detecting, aiming and hitting combat targets at night. In the early days of the development of low-light-level night vision technology, due to cost constraints, the requirements for imaging resolution and image quality were relatively low. However, with the development of fiber-optic image transmission components and the improvement of performance and price stabilization of various electronic products, high-definition low-light-level night vision devices are gradually becoming technically feasible. From ordinary clarity to low-standard clarity, and then to the current high-definition, high-definition low-light-level night vision technology has become the mainstream development trend.
[0003] The high definition of low-light night vision devices includes high resolution and high contrast. The benefit of continuously improving resolution is that more details can be seen, and the improvement of contrast can make the image clearer and more eye-catching. Among them, the impact of contrast on visual effects is very critical. Contrast refers to the degree of contrast between light and dark in the picture. Increasing contrast will make the bright areas in the picture brighter and the dark areas darker, and the contrast between light and dark will be enhanced; the greater the contrast, the clearer and more eye-catching the image will be, while a small contrast will make the entire image gray. High contrast is of great help to the clarity and detail of the image. There are two ways to improve contrast: one is to increase the brightness to increase the contrast. This method is relatively simple, but it is limited by the life of the image tube, light leakage of components, etc. The brightness cannot be increased indefinitely, and the virtual high brightness will also cause the image to be distorted due to high brightness, bringing bad effects; the second is to make the black darker and reduce the minimum brightness to make the contrast between light and dark more obvious. Therefore, whether the low-light-level night vision device can capture sufficiently clear details has a lot to do with the resolution and contrast of the fiber-optic imaging element. Contrast is an important performance indicator of fiber-optic imaging products. At present, the contrast of fiber-optic imaging elements on the market can only reach 3-5%. With the continuous development of fiber-optic imaging technology, the requirements for various product performances are getting higher and higher, and the fiber-optic image inverter is the key material to ensure the imaging quality of the low-light-level night vision device.
[0004] Fiber optic image transmission components include fiber optic panels, fiber optic image invertors, fiber optic light cones, fiber optic image transmission bundles, etc. They are excellent optoelectronic imaging components with large numerical aperture, high light transmission efficiency, high resolution, clear and true image transmission, optically zero thickness, simple structure, small size, light weight, good air tightness, small distortion, few spots, small inter-stage coupling loss, high coupling efficiency, and can improve edge image quality. The most typical application of fiber optic image transmission components is as the optical input and output window of low-light image intensifiers, which plays an important role in improving the quality of imaging devices. They are widely used in various cathode ray tubes, camera tubes, charge-coupled device CCD coupling, medical device displays, high-definition television imaging and other instruments and equipment that need to transmit images in the fields of military, criminal investigation, aerospace, and medical treatment. They are high-tech cutting-edge products in the optoelectronics industry of the current century. The image transmission mechanism of the optical fiber image transmission element is realized by the total reflection principle of the optical fiber. The optical fiber constituting the optical fiber image transmission element is made of a low-refractive index skin glass tube, a high-refractive index core glass rod and a light-absorbing glass filament, which are prepared by hot melting and pressing using a rod-tube combination and a vacuum drawing process. Since the optical fiber is completely tightly fused together by the skin glass, the adjacent optical fibers are close to each other, resulting in cross-light between adjacent fibers. Or due to the uneven temperature field or drawing force during the preparation process, the wall thickness of the skin glass tube may be uneven, which may cause the input light to penetrate the skin glass during the total reflection process and cause light leakage. Or the core or skin contact interface of the optical fiber has defects or contaminants, which destroys the total reflection conditions of the light, causing the light to scatter here. The scattered light enters the adjacent fiber, causing cross-light. The presence of stray light is an important factor that directly affects the imaging quality of the optical fiber image transmission element, such as contrast and clarity.
[0005] In order to solve the above problems, it is usually adopted to fill the gaps between adjacent optical fibers with light-absorbing glass fibers to absorb stray light and improve the imaging quality of optical fiber image transmission elements. Light-absorbing fibers are inserted into the gaps between the arranged optical fibers, and light-absorbing substances are added to the outside of the optical fiber cortex to absorb crosstalk or stray light to achieve optical insulation. This not only absorbs crosstalk, light leakage, etc., but also does not reduce the core-skin area ratio. However, the light-absorbing fiber insertion method cannot completely achieve optical insulation. The key to the above defects is the problem of light-absorbing materials. The requirements for light-absorbing materials are, first, strong light absorption ability in the entire visible light and near-infrared wavelength range, second, a thermal expansion coefficient similar to that of the cortex glass so as to match each other in the process, and third, stable physical and chemical properties, and not prone to crystallization or ion valence changes during processes such as wire drawing, hot melt pressing, and torsion molding. Ordinary light-absorbing glass still has a high transmittance in the visible light range at a thickness of 0.5mm. As the thickness decreases, the transmittance will gradually increase. However, the light-absorbing materials of traditional optical fiber image transmission components generally have problems such as low stray light absorption efficiency and poor imaging contrast. In particular, the light-absorbing glass used in optical fiber image transmission components, after the existing light-absorbing glass is drawn to a fiber diameter of less than or equal to 4.0μm, the colored ions will easily diffuse into the cortex glass, resulting in ion penetration between the glasses, and even the edge of the twisted optical fiber image inverter will turn black or produce fixed pattern noise defects, such as white chicken wire and multifilament shadows, resulting in low quality and finished product qualification rate of the optical fiber image inverter, which cannot meet the batch application requirements of high-definition optical fiber image transmission components. The main reason for this is that the light absorption capacity of the light-absorbing glass material and the fixed pattern noise defect are a set of contradictions. The light absorption capacity of the light-absorbing glass is too strong, and the probability of the fixed pattern noise defect is greater. The light absorption capacity of the light-absorbing glass is too weak, and the effect of improving the contrast of the optical fiber image inverter cannot be achieved. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a high-uniformity optical fiber image invertor capable of improving the contrast and clarity of imaging of an optical fiber image transmission element.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a high-uniformity optical fiber image invertor comprises the following steps:
[0009] (1) preparing a monofilament and a light-absorbing filament: matching a core glass rod with a high refractive index and a skin glass tube with a low refractive index, and then drawing a monofilament to obtain a drawn monofilament, wherein the diameter of the monofilament is 3.0 to 4.0 mm; matching a light-absorbing glass rod with the skin glass tube with a low refractive index, and then drawing a light-absorbing filament, wherein the diameter of the light-absorbing filament is the same as that of the monofilament;
[0010] (2) Preparing a primary multifilament: Arranging the drawn monofilaments into a hexagonal cube with a regular hexagonal cross section, wherein the number of monofilaments on each side of the hexagonal cube is 5 and the total number of monofilaments is 61, and replacing the monofilament arranged in the center of the hexagonal cube with a light absorbing filament to obtain a primary composite rod, and then drawing the primary composite rod into a primary multifilament, wherein the cross section of the primary multifilament is a regular hexagon, and the hexagonal opposite side size of the primary multifilament is 0.99-1.12 mm; when the number of monofilaments on each side is 4 or less, the proportion of the light absorbing material is too high, and fixed pattern noise defects such as white grid and multifilament shadow defects will be generated; when the number of monofilaments on each side is more than 5, the contrast will be reduced, and the high contrast effect cannot be achieved, so it is preferred that the number of monofilaments on each side is 5;
[0011] (3) preparing secondary multifilaments: arranging the primary multifilaments into secondary composite rods with a regular hexagonal cross section, wherein the number of rods on each side of the primary multifilaments is 14, and the total number of rods of the primary multifilaments is 547; drawing the secondary composite rods into secondary multifilaments, wherein the hexagonal opposite side size of the secondary multifilaments is 0.87-0.91 mm; and cutting the secondary multifilaments into fixed lengths and arranging them into plate segments;
[0012] (4) Hot melt pressing: placing the arranged plate segments into a hot melt pressing mold, placing the mold with the plate segments into a hot melt pressing furnace at a high temperature of 450-550°C, and then starting to press the plates according to the designed compression ratio before and after hot melt pressing. The pressing time of hot melt pressing is controlled at 130-180 minutes, thus obtaining an optical fiber plate blank of a high uniformity optical fiber image inverter with a unit wire diameter of ≤4.0 μm;
[0013] (5) Twisting molding: The obtained optical fiber board blank is processed and twisted at an angle of 180° to obtain the desired high-uniformity optical fiber image inverter.
[0014] Furthermore, the method for preparing the light absorbing glass used for the light absorbing wire comprises the following steps:
[0015] (a) Raw material preparation: quartz sand, aluminum oxide, boric acid or boric anhydride, sodium carbonate, potassium carbonate, basic magnesium carbonate, calcium carbonate, zinc oxide, titanium dioxide, zirconium oxide, iron trioxide, cobalt trioxide, vanadium pentoxide and molybdenum oxide are weighed according to a proportion, and mixed evenly to obtain a raw material mixture;
[0016] (b) Glass melting: The raw material mixture is placed in a crucible for high-temperature melting. After the raw material mixture is melted, it is clarified. The molten and clarified glass liquid is cast into a mold into glass of specified specifications. After the glass is cooled and solidified, it is annealed to obtain light absorbing material glass.
[0017] The high temperature melting includes melting at a temperature of 1450-1550° C. for 3-5 hours, and the raw material mixture is stirred 1-2 times during the melting process;
[0018] The clarification temperature is 1300-1400°C, and the clarification time is 1-2 hours;
[0019] The annealing process is to keep the temperature at 500-549°C for 2-3 hours, and then cool it down to room temperature in 20-24 hours;
[0020] Furthermore, it also includes that after the casting is completed and the glass melt has not yet completely solidified, the glass melt is vibrated evenly with an oscillator to remove internal holes and bubbles in the glass melt.
[0021] The light absorbing glass is composed of the following components in molar percentage:
[0022]
[0023]
[0024] Preferably, the light absorbing glass is composed of the following components in molar percentage:
[0025]
[0026] More preferably, the light absorbing glass consists of the following components in molar percentage:
[0027]
[0028]
[0029] The invention also provides a high-uniformity optical fiber image invertor, which is prepared according to the preparation method.
[0030] The high uniformity optical fiber image inverter has a crosstalk of less than 1% at a distance of 0.1 mm from the blade; a resolution of greater than 140 lp / mm; and a spectral transmittance of greater than 70% and a transmittance uniformity of less than 5% within a wavelength range of 400-700 nm.
[0031] The light absorbing material glass has strong and uniform light absorbing ability and spectrum absorbing effect in the wavelength range of 400-700nm at a thickness of 0.3±0.01mm, and the spectrum transmittance is ≤0.1%.
[0032] The present invention further provides an application of the high-uniformity optical fiber image inverter in low-light-level night vision technology. The optical fiber image inverter can be applied to a low-light-level image intensifier.
[0033] The light absorbing material glass of the present invention can be applied to a high-uniformity optical fiber image inverter, and the high-uniform optical fiber image inverter can be applied to a low-light image intensifier. The light absorbing material glass of the present invention is suitable for being used as an outer wall absorption glass material of an optical fiber when preparing an optical fiber image transmission element. The optical fiber image transmission element includes an optical fiber panel, an optical fiber image inverter, an optical fiber light cone, and an optical fiber image transmission bundle, and is particularly suitable for preparing a high-uniformity optical fiber image inverter.
[0034] In the present invention, SiO2 is the main component of the glass skeleton and plays a major role in the glass skeleton. The molar percentage (mol.%) of SiO2 is 60-69.9. When the SiO2 content is lower than 60 mol.%, it is difficult to obtain a thermal expansion coefficient similar to that of the leather glass, and the chemical resistance of the glass will be reduced; when the SiO2 content is higher than 69.9 mol.%, the high-temperature viscosity of the glass will increase, resulting in an excessively high glass melting temperature.
[0035] Al2O3 is an intermediate oxide of glass. 3+ There are two coordination states, namely, located in tetrahedron or octahedron. When there is enough oxygen in the glass, aluminum oxygen tetrahedron [AlO4] is formed, forming a continuous network with silicon oxygen tetrahedron. When there is insufficient oxygen in the glass, aluminum oxygen octahedron [AlO6] is formed, which is an external body of the network and is in the vacancy of the silicon oxygen structure network. Therefore, within a certain content range, it can be the main body of the glass network formed with SiO2. Al2O3 content greater than 10.0 mol.% will significantly increase the high temperature viscosity of the glass and increase the melting temperature of the glass. Therefore, the molar percentage (mol.%) of Al2O3 is 1.0-10.0.
[0036] B2O3 is a glass-forming oxide and a component of the glass skeleton. It is also a solvent that reduces the viscosity of the glass. Boron oxide triangles [BO3] and boron oxide tetrahedrons [BO4] are structural components. Boron may exist in the form of triangles [BO3] or boron oxide tetrahedrons [BO4] under different conditions. Under high-temperature melting conditions, it is generally difficult to form boron oxide tetrahedrons, and can only exist in the form of trihedrons. However, at low temperatures, under certain conditions, B 3+ It has a tendency to capture free oxygen to form tetrahedrons, making the structure compact and increasing the low-temperature viscosity of the glass. However, due to its characteristics of reducing the viscosity of the glass at high temperatures and increasing the viscosity of the glass at low temperatures, it is also the main component that reduces the refractive index of the glass, which determines that its content range is relatively small. The molar percentage (mol.%) of B2O3 is 10.1-15.0. When the content of B2O3 is greater than 15.0mol.%, the refractive index of the glass will be reduced and the phase separation tendency of the glass will be increased.
[0037] Na2O is an oxide outside the glass structure network. When the content of Na2O is greater than 8.0 mol.%, it will increase the thermal expansion coefficient of the glass and increase the refractive index of the glass. Therefore, the molar percentage (mol.%) of Na2O is 1.0-8.0.
[0038] K2O is an oxide outside the glass structure network. When the content of K2O is greater than 10.0 mol.%, the thermal expansion coefficient of the glass will increase, and at the same time, the refractive index of the glass will be increased. Therefore, the molar percentage (mol.%) of K2O is 3.0-10.0.
[0039] MgO is an external oxide of the glass structure network. When the content of MgO is greater than 1.0 mol%, it will increase the crystallization tendency of the glass, while reducing the density of the glass and increasing the refractive index of the glass. Therefore, the molar percentage (mol.%) of MgO is 0.1-1.0.
[0040] CaO is an external oxide of the glass structure network. When the content of CaO is greater than 5.0 mol%, it will reduce the chemical stability of the glass, increase the refractive index of the glass, and increase the crystallization tendency of the glass. Therefore, the molar percentage (mol.%) of CaO is 0.5-5.0.
[0041] ZnO is used to adjust the crystallization temperature and chemical stability of glass. The molar percentage of ZnO is 0-0.1 mol%. If the content of ZnO is greater than 0.1 mol%, the chemical stability of glass will be reduced and the crystallization tendency will be increased.
[0042] TiO2 is used to adjust the chemical resistance and crystallization of glass. The molar percentage (mol.%) of TiO2 is 0-0.1. If the TiO2 content is greater than 0.1 mol.%, the chemical resistance of the glass will be reduced and the crystallization tendency will be increased.
[0043] ZrO2 is used to adjust the chemical resistance and crystallization of glass. The molar percentage (mol.%) of ZrO2 is 0.1-1.0. If the content of ZrO2 is greater than 1.0 mol.%, the chemical resistance of glass will be reduced and the crystallization tendency will be increased.
[0044] Fe2O3 is a light absorbing colorant in light absorbing glass. The molar percentage (mol.%) of Fe2O3 is 3.0-6.5. In the present invention, Fe2O3 is the main light absorbing agent. 3+The ions have good light absorption properties, and the absorption range is mainly concentrated in the visible light to infrared region. When the content of Fe2O3 is greater than 6.5mol%, it will reduce the chemical stability of the glass and increase the crystallization tendency of the glass. When the content of Fe2O3 is less than 3.0mol%, the coloring of Fe2O3 will become unstable or even fade during the high-temperature drawing process, which will directly affect the light absorption effect and have a serious impact on improving the image transmission quality of the optical fiber image inverter, and cannot meet the application requirements of improving the contrast of the optical fiber image inverter.
[0045] Co2O3 is a colorant for light-absorbing glass. The molar percentage (mol.%) of Co2O3 is 0.1-0.5. Co2O3 can combine with iron ions to form a stable form in the glass, thereby making the coloring of the light-absorbing material more stable. When the content of Co2O3 is greater than 0.5 mol.%, it will reduce the chemical stability of the glass and increase the tendency of the glass to crystallize.
[0046] V2O5 is a colorant for light-absorbing glass. The molar percentage (mol.%) of V2O5 is 0.51-1.5. V2O5 can solidify the coloring of iron ions, thereby making the coloring of light-absorbing materials more stable. When the content of V2O5 is greater than 1.5 mol.%, it will reduce the chemical stability of the glass and increase the tendency of glass to crystallize.
[0047] MoO3 is a transition metal oxide and also a colorant for light-absorbing glass. The molar percentage (mol.%) of MoO3 is 0.1-1.0. MoO3 can combine with iron ions and cobalt ions to form a stable coloring in the glass. If the content of MoO3 is greater than 1.0 mol.%, it will reduce the chemical resistance of the glass and increase the crystallization tendency of the glass.
[0048] Compared with the prior art, the light absorbing glass used in the high uniformity optical fiber image invertor of the present invention has the following characteristics:
[0049] (1) It has good light absorption performance, with strong and uniform light absorption ability and spectral absorption effect in the wavelength range of 400-700nm at a thickness of 0.3±0.01mm, and the spectral transmittance is ≤0.1%;
[0050] (2) It has similar thermal expansion coefficient and viscosity characteristics to leather glass. The thermal expansion coefficient of glass is (82±2)×10 -7 / ℃;
[0051] (3) It has good chemical stability and anti-crystallization performance. After the light-absorbing glass is melted, there are no stones, bubbles or holes inside. It does not separate into phases or crystallize when kept at 820℃ for 6 hours. It has good anti-crystallization performance and excellent chemical stability.
[0052] The high uniformity optical fiber image invertor of the present invention prepared by using the above-mentioned light absorbing glass has the following characteristics:
[0053] (1) The crosstalk of the high uniformity optical fiber image invertor is less than 1.0% at a distance of 0.1 mm from the blade edge;
[0054] (2) The resolution of the high uniformity fiber image invertor is greater than 140lp / mm;
[0055] (3) The high uniformity fiber image invertor has excellent fixed pattern noise performance, and no obvious multifilament boundary is observed under a 10x microscope;
[0056] (4) The high-uniformity optical fiber image invertor has a transmittance of more than 70% in the wavelength range of 400-700 nm, a transmittance uniformity of less than 5%, few spot defects, and no aggregated spot defects.
[0057] (5) The light absorbing glass of the present invention is used in a fiber optic image inverter, which can effectively improve the absorption of stray light between optical fibers to reduce crosstalk between fibers, thereby achieving the effect of improving the contrast and clarity of the fiber optic image inverter imaging.
[0058] The invention reduces the diameter of the optical fiber through the insertion and adjustment of the light absorbing wire, improves the resolution of the optical fiber image inverter, makes the resolution of the optical fiber image inverter greater than 140lp / mm, and improves the contrast of the optical fiber image inverter, makes the crosstalk of the optical fiber image inverter less than 1% at a distance of 0.1mm from the knife edge, thereby preparing a high-definition optical fiber image inverter. The high-uniformity optical fiber image inverter of the invention has the advantages of less stray light crosstalk, high resolution, high contrast, and simple preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] The present invention will be further described below in conjunction with the accompanying drawings and implementation modes.
[0060] Figure 1 A schematic diagram of the internal structure of an optical fiber of a high-definition optical fiber image inverter provided by an embodiment of the present invention;
[0061] Figure 2 A schematic diagram of the optical fiber structure provided by an embodiment of the present invention;
[0062] Figure 3 This is a contrast test chart of the high uniformity optical fiber image inverter prepared by Example 1 of the present invention.
[0063] Among them, 1 is light absorbing glass, 2 is core glass, and 3 is skin glass. DETAILED DESCRIPTION
[0064] In order to make the purpose, technical solution and advantages of the present invention clearer, the embodiments of the present invention are further described in detail below. The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but it is not intended to limit the present invention.
[0065] See also Figure 1 and Figure 2 The skin glass tube and the core glass rod are matched and drawn into a single wire, the single wire includes an outer skin glass 3 and an inner core glass 2, and after arranging 5 single wires on each side into a composite rod with a hexagonal cross section, the light absorbing material glass rod and the skin glass tube are matched and drawn into a light absorbing wire, the light absorbing wire includes an outer skin glass 3 and an inner light absorbing material glass 1, and is drawn after the light absorbing material glass rod is covered with a skin glass tube, and a single wire at the center of the composite rod is replaced with a light absorbing wire to form a composite rod, and the composite rod is drawn into Figure 1 The primary multifilament shown in the figure. The method of using the light absorbing filaments drawn by the present invention to replace the single filaments can effectively absorb the crosstalk inside the optical fiber and improve the contrast. In the figure, the hexagonal side size L of the primary multifilament with a regular hexagonal cross section is 0.99-1.12mm.
[0066] In this article, all "mol. %" are based on the total molar amount of the final glass composition. The glass chemical composition (mol. %) of the embodiment is listed in detail in Table 1. Among them, the light transmittance of the glass at 400nm-700nm is measured by a transmittance tester, and the thickness of the glass sheet is 0.3mm±0.01mm; the crystallization temperature is measured by a gradient crystallization furnace; the linear expansion coefficient α of 30-300℃ 30 / 300 [10 -7 / ℃] is measured using a horizontal dilatometer and expressed as the average linear expansion coefficient using the method specified in ISO7991.
[0067] Table 1 Chemical composition (mol.%) and glass properties of the examples
[0068]
[0069]
[0070] The raw materials and raw material requirements used in the following examples are as follows:
[0071] Quartz sand or crystal powder (high purity, 150μm sieve content is less than 1%, 45μm sieve content is less than 30%, Fe2O3 content is less than 1ppm), alumina powder (analytical grade, average particle size 50μm), boric acid or boric anhydride (400μm sieve content is less than 10%, 63μm sieve content is less than 10%), sodium carbonate (industrial soda ash), potassium carbonate (analytical grade, purity ≥99.0%), basic magnesium carbonate (chemically pure, average particle size 50μm), calcium carbonate (analytical grade, average particle size 250μm), zinc oxide (analytical grade), titanium dioxide (analytical grade), zirconium oxide (analytical grade), ferric oxide (analytical grade), vanadium oxide (analytical grade), molybdenum oxide (analytical grade).
[0072] Example 1
[0073] Preparation of light absorbing glass:
[0074] First, select the raw materials according to the glass composition of Example 1 in Table 1, and make the ingredients meet the glass chemical composition of Table 1. Then use a quartz crucible to melt at 1500°C for 4 hours. During the glass melting process, stir the glass 1 to 2 times to make the glass melt evenly. After the glass is melted, clarify the glass melt at 1350°C for 2 hours. Cast the molten glass into the specified specifications. After the casting is completed, when the glass melt has not completely solidified, vibrate the glass melt evenly with an oscillator to remove the internal holes and bubbles in the glass melt. After the glass rod is cooled and solidified, annealing is performed. The annealing process is to keep it at 530°C for 2 hours and then cool it to room temperature in 24 hours to obtain the light absorbing glass of the present invention. The basic properties of the sample are shown in Table 1. The visible light transmittance of the sample with a thickness of 0.3mm is 0%, and the thermal expansion coefficient is 80×10 -7 / ℃.
[0075] Method for preparing high uniformity optical fiber image invertor using light absorbing glass:
[0076] (1) matching a core glass rod with a refractive index of 1.81 and a skin glass tube with a refractive index of 1.49 to draw a single wire to obtain a drawn single wire with a wire diameter of 3.20 mm; matching a light absorbing glass rod with a skin glass tube with a refractive index of 1.49 to draw a light absorbing wire with a wire diameter of 3.20 mm;
[0077] (2) Arranging the drawn monofilaments into a hexagon with a regular hexagonal cross section, wherein the number of monofilaments on each side of the hexagon is 5, and the total number of monofilaments in the primary composite rod formed by the monofilaments is 61, and replacing the monofilament arranged in the center of the hexagon with a light absorbing filament to obtain a primary composite rod, and then drawing the primary composite rod into a primary multifilament, wherein the cross section of the primary multifilament is a regular hexagon, and the hexagonal opposite side dimension L of the primary multifilament is 1.10 mm;
[0078] (3) Arranging the primary multifilaments into a secondary composite rod with a regular hexagonal cross section as required, the number of primary multifilament rods per side being 14, and the total number of primary multifilament rods being 547, drawing the secondary composite rod into a secondary multifilament with a regular hexagonal cross section, the hexagonal opposite side dimension of the secondary multifilament being 0.91 mm, and then cutting the secondary multifilaments to a fixed length and arranging them into plate segments;
[0079] (4) Hot melt pressing: placing the plate segment into a hot melt pressing mold, placing the mold with the plate segment into a hot melt pressing furnace at a high temperature of 500°C, and then starting to press the plate according to the designed compression ratio before and after hot melt pressing. The pressing time of hot melt pressing is controlled at 150 minutes, and an optical fiber plate blank of a high uniformity optical fiber image inverter with a unit wire diameter of 3.98 μm is obtained;
[0080] (5) Twisting molding: The obtained optical fiber board blank is processed and twisted at an angle of 180° to obtain the required high-uniformity optical fiber image inverter.
[0081] See also Figure 3 The contrast performance test of the high-uniformity optical fiber image inverter prepared by the above-mentioned light-absorbing glass shows that the crosstalk of the high-uniform optical fiber image inverter prepared by the above-mentioned light-absorbing glass is 0.82% at a distance of 0.1mm from the blade, the resolution of the prepared optical fiber image inverter is 144lp / mm, and the spectral transmittance of the prepared optical fiber image inverter within the wavelength range of 400-700nm is 72%. Applying the above-mentioned high-uniformity optical fiber image inverter to the low-light image intensifier can significantly improve the contrast and resolution of the low-light image intensifier.
[0082] Example 2
[0083] Preparation of light absorbing glass:
[0084] The actual composition of the glass is shown in Example 2 in Table 1. The same raw materials and raw material requirements as those in Example 1 are used. Then, a quartz crucible is used to melt the glass at 1450°C for 5 hours. During the glass melting process, the glass is stirred 1 to 2 times to make the glass melt evenly. After the glass is melted, the glass melt is clarified at 1400°C for 1 hour. The molten glass liquid is cast into a specified specification and vibrated evenly before annealing. The annealing process is to keep the temperature at 525°C for 2.5 hours and then cool it to room temperature for 20 hours, thus obtaining the light absorbing glass of the present invention. The basic properties of the sample are shown in Table 1. The visible light transmittance of the sample with a thickness of 0.3 mm is 0%, and the thermal expansion coefficient is 81×10 -7 / ℃.
[0085] Method for preparing high uniformity optical fiber image invertor using light absorbing glass:
[0086] (1) matching a core glass rod with a refractive index of 1.81 and a skin glass tube with a refractive index of 1.48 to draw a single wire to obtain a drawn single wire, and the single wire diameter is 3.0 mm; matching a light absorbing glass rod with a skin glass tube with a refractive index of 1.48 to draw a light absorbing wire, and the wire diameter of the light absorbing wire is 3.0 mm;
[0087] (2) Arranging the drawn monofilaments into a hexagonal body with a regular hexagonal cross section, wherein the number of monofilaments on each side of the hexagonal body is 5, and the total number of monofilaments in the primary composite rod formed by the monofilaments is 61, and replacing the monofilament arranged in the center of the hexagonal body with a light absorbing filament to obtain a primary composite rod, and then drawing the primary composite rod into a primary multifilament with a regular hexagonal cross section, wherein the hexagonal opposite side size of the primary multifilament is 0.99 mm;
[0088] (3) Arranging the primary multifilaments into a secondary composite rod with a regular hexagonal cross section as required, the number of primary multifilament rods per side being 14, and the total number of primary multifilament rods being 547, and drawing the secondary composite rod into a secondary multifilament with a regular hexagonal cross section, the hexagonal opposite side dimension of the secondary multifilament being 0.87 mm, and then cutting the secondary multifilaments to a fixed length and arranging them into plate segments;
[0089] (4) Hot melt pressing: placing the plate segment into a hot melt pressing mold, placing the mold with the plate segment into a hot melt pressing furnace at a high temperature of 450°C, and then starting to press the plate according to the designed compression ratio before and after hot melt pressing of the plate segment. The pressing time of hot melt pressing is controlled at 180 minutes, and thus an optical fiber plate blank of a high uniformity optical fiber image inverter with a unit wire diameter of 3.80 μm is obtained;
[0090] (5) Twisting molding: The obtained optical fiber board blank is processed and twisted at an angle of 180° to obtain the required high-uniformity optical fiber image inverter.
[0091] The prepared high-uniformity optical fiber image inverter has a crosstalk of 0.80% at a distance of 0.1mm from the blade, a resolution of 144lp / mm, and a spectral transmittance of 72% within the wavelength range of 400-700nm. Applying the prepared high-uniformity optical fiber image inverter to a low-light level image intensifier can significantly improve the contrast and resolution of the low-light level image intensifier.
[0092] Example 3
[0093] The actual composition of the glass is shown in Example 3 in Table 1. The same raw materials and raw material requirements as those in Example 1 are used. Then, a quartz crucible is used to melt the glass at 1550°C for 3 hours. During the glass melting process, the glass is stirred 1 to 2 times to make the glass melt evenly. After the glass is melted, the glass melt is clarified at 1300°C for 2 hours. The molten glass is cast into a specified specification and annealed. The annealing process is to keep the temperature at 540°C for 3 hours and then cool it to room temperature for 21 hours, thus obtaining the light absorbing glass of the present invention. The basic properties of the sample are shown in Table 1. The visible light transmittance of the sample with a thickness of 0.3 mm is 0%, and the thermal expansion coefficient is 84×10 -7 / ℃.
[0094] Method for preparing high uniformity optical fiber image invertor using light absorbing glass:
[0095] (1) matching a core glass rod with a refractive index of 1.81 and a skin glass tube with a refractive index of 1.49 to draw a single wire to obtain a drawn single wire, and the single wire diameter is 4.0 mm; matching a light absorbing glass rod with a skin glass tube with a refractive index of 1.49 to draw a light absorbing wire, and the wire diameter of the light absorbing wire is 4.0 mm;
[0096] (2) arranging the drawn monofilaments into a hexagonal body with a regular hexagonal cross section, wherein the number of monofilaments on each side of the hexagonal body is 5 and the total number of monofilaments is 61, and replacing the monofilament arranged at the center of the hexagonal body with a light absorbing filament to obtain a primary composite rod, and then drawing the primary composite rod into a primary multifilament with a regular hexagonal cross section, wherein the hexagonal opposite side size of the primary multifilament is 1.12 mm;
[0097] (3) Arranging the primary multifilaments into a secondary composite rod with a regular hexagonal cross section as required, the number of primary multifilament rods per side being 14, and the total number of primary multifilament rods being 547, drawing the secondary composite rod into a secondary multifilament with a regular hexagonal cross section, the hexagonal opposite side dimension of the secondary multifilament being 0.89 mm, and then cutting the secondary multifilaments to a fixed length and arranging them into plate segments;
[0098] (4) Hot melt pressing: placing the plate segment into a hot melt pressing mold, placing the mold with the plate segment into a hot melt pressing furnace at a high temperature of 550°C, and then starting to press the plate according to the designed compression ratio before and after hot melt pressing. The pressing time of hot melt pressing is controlled at 130 minutes, and thus an optical fiber plate blank of a high uniformity optical fiber image inverter with a unit wire diameter of 3.89 μm is obtained;
[0099] (5) Twisting molding: The obtained optical fiber board blank is processed and twisted at an angle of 180° to obtain the required high-uniformity optical fiber image inverter.
[0100] The prepared high-uniformity optical fiber image inverter has a crosstalk of 0.86% at a distance of 0.1mm from the blade, a resolution of 144lp / mm, and a spectral transmittance of 72% within the wavelength range of 400-700nm. Applying the prepared high-uniformity optical fiber image inverter to a low-light level image intensifier can significantly improve the contrast and resolution of the low-light level image intensifier.
[0101] Example 4
[0102] The actual composition of the glass is shown in Example 4 in Table 1. The same raw materials and raw material requirements as those in Example 1 are used. Then, a quartz crucible is used to melt the glass at 1480°C for 5 hours. During the glass melting process, the glass is stirred 1 to 2 times to make the glass melt evenly. After the glass is melted, the glass melt is clarified at 1380°C for 1.5 hours. The molten glass is cast into a specified specification and annealed. The annealing process is to keep the temperature at 500°C for 2.5 hours and then cool it to room temperature for 22 hours, thus obtaining the light absorbing glass of the present invention. The basic properties of the sample are shown in Table 1. The visible light transmittance of the sample with a thickness of 0.3 mm is 0%, and the thermal expansion coefficient is 84×10 -7 / ℃.
[0103] The method for preparing a high-uniformity optical fiber image inverter using light-absorbing glass is as shown in Example 1. The prepared high-uniform optical fiber image inverter has a crosstalk of 0.89% at 0.1 mm from the blade, a resolution of 144 lp / mm, and a spectral transmittance of 71% within the wavelength range of 400-700 nm. The high-uniformity optical fiber image inverter prepared is applied to a low-light image intensifier, which can significantly improve the contrast and resolution of the low-light image intensifier.
[0104] Example 5
[0105] The actual composition of the glass is shown in Example 5 in Table 1. The same raw materials and raw material requirements as those in Example 1 are used. Then, a quartz crucible is used to melt the glass at 1460°C for 4 hours. During the glass melting process, the glass is stirred 1 to 2 times to make the glass melt uniform. After the glass is melted, the glass melt is clarified at 1350°C for 2 hours. The molten glass is cast into a specified specification and annealed. The annealing process is to keep the temperature at 549°C for 3 hours and then cool it to room temperature for 20 hours, thus obtaining the light absorbing glass of the present invention. The basic properties of the sample are shown in Table 1. The visible light transmittance of the sample with a thickness of 0.3 mm is 0%, and the thermal expansion coefficient is 83×10 -7 / ℃.
[0106] The method for preparing a high-uniformity optical fiber image inverter using light-absorbing glass is as shown in Example 1. The prepared high-uniform optical fiber image inverter has a crosstalk of 0.90% at 0.1 mm from the blade, a resolution of 144 lp / mm, and a spectral transmittance of 71% within the wavelength range of 400-700 nm. The high-uniformity optical fiber image inverter prepared is applied to a low-light image intensifier, which can significantly improve the contrast and resolution of the low-light image intensifier.
[0107] Example 6
[0108] The actual composition of the glass is shown in Example 5 in Table 1. The same raw materials and raw material requirements as those in Example 1 are used. Then, a quartz crucible is used to melt the glass at 1470°C for 5 hours. During the glass melting process, the glass is stirred 1 to 2 times to make the glass melt evenly. After the glass is melted, the glass melt is clarified at 1370°C for 2 hours. The molten glass is cast into a specified specification and annealed. The annealing process is to keep the temperature at 540°C for 3 hours and then cool it to room temperature within 24 hours, thus obtaining the light absorbing glass of the present invention. The basic properties of the sample are shown in Table 1. The visible light transmittance of the sample with a thickness of 0.3 mm is 0%, and the thermal expansion coefficient is 82×10 -7 / ℃.
[0109] The method for preparing a high-uniformity optical fiber image inverter using light-absorbing glass is as shown in Example 1. The prepared high-uniform optical fiber image inverter has a crosstalk of 0.92% at 0.1 mm from the blade, a resolution of 144 lp / mm, and a spectral transmittance of 71% within the wavelength range of 400-700 nm. The high-uniformity optical fiber image inverter prepared is applied to a low-light image intensifier, which can significantly improve the contrast and resolution of the low-light image intensifier.
[0110] The present invention also provides an application of a high-uniformity optical fiber image invertor in a low-light-level image intensifier, so that the high-uniformity optical fiber image invertor can be widely used in low-light-level night vision technology.
[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high uniformity optical fiber image invertor, characterized in that: The following steps are involved: (1) preparing a monofilament and a light-absorbing filament: matching a core glass rod with a high refractive index and a skin glass tube with a low refractive index, and then drawing a monofilament to obtain a drawn monofilament, wherein the diameter of the monofilament is 3.0 to 4.0 mm; matching a light-absorbing glass rod with the skin glass tube with a low refractive index, and then drawing a light-absorbing filament, wherein the diameter of the light-absorbing filament is the same as that of the monofilament; (2) preparing a primary multifilament: arranging the drawn monofilaments into a hexagonal body with a regular hexagonal cross section, wherein the number of monofilaments on each side of the hexagonal body is 5 and the total number of monofilaments is 61, and replacing the monofilament arranged at the center of the hexagonal body with a light absorbing filament to obtain a primary composite rod, and then drawing the primary composite rod into a primary multifilament, wherein the cross section of the primary multifilament is a regular hexagonal body, and the hexagonal opposite side size of the primary multifilament is 0.99-1.12 mm; (3) preparing secondary multifilaments: arranging the primary multifilaments into secondary composite rods with a regular hexagonal cross section, wherein the number of rods on each side of the primary multifilaments is 14, and the total number of rods of the primary multifilaments is 547; drawing the secondary composite rods into secondary multifilaments, wherein the hexagonal opposite side size of the secondary multifilaments is 0.87-0.91 mm; and cutting the secondary multifilaments into fixed lengths and arranging them into plate segments; (4) Hot melt pressing: placing the arranged plate segments into a hot melt pressing mold, placing the mold with the plate segments into a hot melt pressing furnace at a high temperature of 450-550°C, and then starting to press the plates according to the designed compression ratio before and after hot melt pressing. The pressing time of hot melt pressing is controlled at 130-180 minutes, thus obtaining an optical fiber plate blank of a high uniformity optical fiber image inverter with a unit wire diameter of ≤4.0 μm; (5) Twisting forming: The obtained optical fiber sheet blank is processed and twisted at an angle of 180° to obtain a high uniformity optical fiber image invertor; The light absorbing glass is composed of the following components in molar percentage: SiO2 60.0-69.9% Al2O3 1.0-10.0% B2O3 10.1-15.0% Na2O 1.0-8.0% K2O 3.0-10.0% MgO 0.1-1.0% CaO 0.5-5.0% ZnO 0-0.1% TiO2 0-0.1% ZrO2 0.1-1.0% Fe2O3 3.0-6.5% Co2O3 0.1-0.5% V2O5 0.51-1.5% MoO3 0.1-1.0%.
2. The preparation method according to claim 1, characterized in that: The method for preparing the light absorbing material glass used for the light absorbing wire comprises the following steps: (a) Raw material preparation: quartz sand, aluminum oxide, boric acid or boric anhydride, sodium carbonate, potassium carbonate, basic magnesium carbonate, calcium carbonate, zinc oxide, titanium dioxide, zirconium oxide, iron trioxide, cobalt trioxide, vanadium pentoxide and molybdenum oxide are weighed according to a proportion, and mixed evenly to obtain a raw material mixture; (b) Glass melting: The raw material mixture is placed in a crucible for high-temperature melting. After the raw material mixture is melted, it is clarified. The molten and clarified glass liquid is cast into a mold into glass of specified specifications. After the glass is cooled and solidified, it is annealed to obtain light absorbing material glass.
3. The preparation method according to claim 2, characterized in that: The high temperature melting includes melting at a temperature of 1450-1550° C. for 3-5 hours, and the raw material mixture is stirred 1-2 times during the melting process; The clarification temperature is 1300-1400°C, and the clarification time is 1-2 hours; The annealing process is to keep the temperature at 500-549°C for 2-3 hours, and then cool it down to room temperature in 20-24 hours; It also includes vibrating the molten glass evenly with an oscillator when the molten glass has not yet completely solidified after casting is completed, so as to remove internal holes and bubbles in the molten glass.
4. The preparation method according to claim 3, characterized in that: The light absorbing glass is composed of the following components in molar percentage: SiO2 60.0-65.0% Al2O3 3.0-6.0% B2O3 11.0-15.0% Na2O 5.0-8.0% K2O 3.0-8.0% MgO 0.1-1.0% 5. The preparation method according to claim 4, characterized in that: The light absorbing glass is composed of the following components in molar percentage:
6. A high uniformity optical fiber image invertor, characterized in that: It is prepared according to the preparation method according to any one of claims 1 to 5.
7. The high uniformity optical fiber image invertor according to claim 6, characterized in that: The high uniformity optical fiber image inverter has a crosstalk of less than 1% at a distance of 0.1 mm from the blade; a resolution of greater than 140 lp / mm; and a spectral transmittance of greater than 70% and a transmittance uniformity of less than 5% within a wavelength range of 400-700 nm.
8. The high uniformity optical fiber image invertor according to claim 7, characterized in that: The light absorbing material glass has strong and uniform light absorbing ability and spectrum absorbing effect in the wavelength range of 400-700nm at a thickness of 0.3±0.01mm, and the spectrum transmittance is ≤0.1%.
9. Use of the high uniformity optical fiber image invertor according to claim 6, 7 or 8 in a low light level image intensifier.
Citation Information
Patent Citations
High-definition optical fiber image inverter and preparation method and application thereof
CN111393023A
Optical fiber type endoscope and preparation method and application thereof
CN113777772A